Cronación y caracterización de la región promotora del integrón de clase 1 predominante en Colombia, Intl1-Col1 (2024)
Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) is a causative agent of gastroenteritis outbreaks, whose clinical relevance has increased due to the emergence of antimicrobial-resistant isolates. In Colombia, the class 1 integron IntI1-Col1 has been predominant in non-invasive clinical isolates since 1997, containing the gene cassette dfr7-aacA-blaOXA-2. The type of promoter regulating the expression of these genes, as well as whether their expression is constitutive or depends on external factors such as antibiotics or environmental conditions, remains unknown.